(untitled) - OLIVIA NELLAWATI, SYANTIA; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this research to analyze the effect of inflation, exchange rate, money supply, gross domestic product, gold price, oil price, fed rate, index Nikkei 225 and index Hang Seng to Indonesia Composite Index period 2012- 2016. This study uses the ratio of changes every month to obtain the sample number is 60. The method of analysis used is multiple linear regression analysis conducted by using SPSS 22. The result of this research in partial show that inflation, money supply, gross domestic product, gold price, oil price, fed rate, and index Hang Seng have not effect to Indonesia Composite Index. Meanwhile exchange rate has negative relation and index Nikkei 225 has positive relation with Indonesia Composite Index. Then all independent variables are simultaneously have effect Indonesia Composite Index. After this research explain determinate which have effect Indonesia Composite Index in 61,7% while the rest of 38,3% described by other variables outside model this research. Keywords: Indonesia Composite Index. Macroeconomics, Gold Price, Oil Price, Global Index